(untitled) (Bangladesh Veterinarian, 2011)
The present study was undertaken to estimate the heritability for growth traits in a nucleus herd of Red Chittagong cattle (RCC) using data from 2005 to 2010. The traits considered were birth weight, weight at three-month intervals from birth to 24 months, and pre-weaning and post-weaning growth rate. The mean pooled weight (mean ± se) of 127 RCC calves from birth to 24 months at three month intervals were 14.7 ± 0.2, 29.3 ± 6.1, 42.6 ± 9.2, 55.0 ± 12.4, 66.2 ± 15.5, 74.5 ± 16.0, 86.1 ± 23.5, 98.8 ± 24.8 and 111.6 ± 25.2 kg, respectively. The pre- and post-weaning growth rates were 148.5 ± 45.0 and 116.6 ± 56.5 g/day, respectively. The pre-weaning growth rate was significantly (P<0.01) higher than post-weaning. For the estimation of heritability single trait animal models under Residual Maximum Likelihood (REML) analyses were done considering sex, parity, season and year of birth as fixed effect and animal’s additive genetic as random effect. Estimates of heritability for weight at birth, 3, 6, 9, 12, 15, 18, 21 and 24 month of age were 0.48 ± 0.04, 0.49 ± 0.06, 0.50 ± 0.08, 0.47 ± 0.06, 0.50 ± 0.08, 0.50 ± 0.33, 0.44 ± 0.14, 0.50 ± 0.11 and 0.50 ± 0.15, respectively. Heritability estimates for pre- and post-weaning growth rate were 0.48 ± 0.06 and 0.49 ± 0.17, respectively. This moderately high heritability of growth of RCC suggests that RCC selected for growth up to 24 months of age would show a quick response. DOI: http://dx.doi.org/10.3329/bvet.v28i1.8812 Bangl. vet. 2011. Vol. 28, No. 1, 39-46